Analysis of Company Value and Financial Performance as Intervening Variables in Property, Real Estate and Building Construction Companies on the Indonesia Stock Exchange - Ramadhani , Brillianto Adhie; Nur, Dhani Ichsanuddin (International Journal of Economics (IJEC), 2024)
This study aims to determine the effect of leverage and investment decisions on company value with financial performance as an intervening variable in property, real estate & building construction sector companies listed on the Indonesia Stock Exchange in 2017-2020. This type of research is associative clause. The population used in this study are property, real estate & building construction companies listed on the Indonesia Stock Exchange in 2017-2020. The type of data used in this study is secondary data and data collection using the documentation method. While taking samples in this study using purposive sampling technique. The research population data totaled 97 companies and obtained a sample of 61 companies so that the research data totaled 204 after going through the outlier test. The data analysis technique used is path analysis. The results of the study show that 1.) Leverage has no effect on firm value; 2.) Investment decisions have an effect on firm value; 3.) Leverage has no effect on firm value through financial performance; 4.) Investment decisions have no effect on firm value through financial performance.